1987
DOI: 10.1016/0035-9203(87)90296-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic splenomegaly in Nairobi, Kenya. I. Epidemiology, malarial antibody and immunoglobulin levels

Abstract: Chronic splenomegaly in 131 Kenyan patients was investigated at Kenyatta National Hospital, Nairobi. Patients were allocated to diagnostic groups on the basis of clinical, haematological, parasitological, histological, radiological and endoscopic data. The major diagnostic groups were hyper-reactive malarial splenomegaly, our preferred name for tropical splenomegaly syndrome, (31%), hepatosplenic schistosomiasis (18%), visceral leishmaniasis (5%) and "indeterminate splenomegaly", where no diagnosis could be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The proportion of patients for the hematologic, hepatic, and ID diseases associated with splenomegaly from Stanford contrasted greatly with those from nearby VMC and confirmed the impact of clinical locale on the diseases associated with splenomegaly [1]. Splenomegaly is an important physical finding because it is usually associated with disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The proportion of patients for the hematologic, hepatic, and ID diseases associated with splenomegaly from Stanford contrasted greatly with those from nearby VMC and confirmed the impact of clinical locale on the diseases associated with splenomegaly [1]. Splenomegaly is an important physical finding because it is usually associated with disease.…”
Section: Discussionmentioning
confidence: 98%
“…The diseases associated with splenomegaly usually depend upon both geographic and clinical locale [1]. Previous studies in the USA on diagnostic evaluation for splenomegaly occurred decades ago only from private office practices [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…The poor model fits for the regression analyses of the left liver lobe for both the ultrasound cohort as a whole and for children with detectable S. mansoni eggs does indicate that although S. mansoni infection and chronic exposure to P. falciparum may contribute to hepatomegaly, some other environmental agent in the study area may be contributing to the hepatomegaly in these children. Kamba Tribe members are more susceptible to portal hypertension and splenomegaly than other tribes within Kenya (De Cock et al. 1987a,b), perhaps because they are exposed to an environmental cause of hepatosplenomegaly and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…One prevailing suggestion has been that hepatosplenomegaly amongst younger children is attributable to malaria infection, whereas older children have acquired some level of immunity to malaria and hence if they do have hepatosplenomegaly it is likely to be attributable to schistosomiasis [6]. However, chronic splenomegaly associated with portal hypertension has been reported in Kenyan hospitals amongst residents from areas where both S. mansoni and malaria infections are endemic [7,8], and it has long been suggested that the presence of both infections may confound attempts to quantify the impact of either one [9,10]. Recently, it was observed that IgG3 antibody responses to P. falciparum schizont antigen (Pfs Ag) were higher in Kenyan children with S. mansoni infection and hepatosplenomegaly compared with children with infection but no hepatosplenomegaly [11], further implicating exposure to malaria in childhood as a risk factor for severe hepatosplenic morbidity.…”
Section: Introductionmentioning
confidence: 99%